Kajian Historis Madrasah Nizamiyah - Apriliani Kartini; Fauzan Fauzan (AZKIA: Journal of Islamic Education in Asia, 2024)
This article aims to outline the study of the establishment of this madrasah with educational elements. In its growth and development, the madrasah is seen as an evolution of Islamic educational institutions. The Nizamiyah Madrasah is the largest madrasah within the educational institutions managed by the Seljuk Dynasty government. This study is qualitative in nature. With the object of study in this article, this type of research falls into the category of library research. The results of this research explain: 1) The History of the Establishment of the Nizamiyah Madrasah, 2) Madrasah as a Dominant Islamic Educational Institution, 3) Development of the Nizamiyah Madrasah Curriculum, 4) The Nizamiyah Madrasah as an Educational Institution, 5) The Nizamiyah Madrasah as a Political-Ideological Battlefield, 6) Founding Figures of the Nizamiyah Madrasah, 7) The Influence of the Nizamiyah Madrasah based on the institution's compatibility with the environment and beliefs in social and religious contexts.